DESAIN MODEL SPESIFIKASI AKSES PENGGUNA DI LINGKUNGAN JARINGAN BERKECEPATAN RENDAH - Wardani, Ratna; Soesianto, F.; Nugroho, Lukito Edi; Ashari, Ahmad (Universitas Ahmad Dahlan, 2010)
The Internet has the potential to provide universal and easy access to the various types of information services on a single multi-service, but unreliable quality connection can sometime prevent access to the Internet altogether. There are many efforts have been started to resolve the Internet access problem. The main idea behind them is to provide a set of objective parameters that can be used to compare and negotiate in a network. Relatively little emphasis has been put on issues concerning end users, especially on the relationship of user perception and Quality of Service parameters. In order to implement Quality of Service schemes successfully, users must be taken into account to establish users subjective perceptions of Quality of Service.This paper is concerned to the study of mechanism of providing Quality of Service specification for Internet access in low-quality connection. We propose the conceptual model for the specification of user access and allow the users to specify their subjective preferences through the Quality of Service parameters. This model provides the alternative option for user access if resource availability in the system is limited. The user is given opportunity to define their access and determine the parameter for each application which they are chosen. The system will check the resource availability and then compare to the user preferences. In the case resource availability is lower than user preferences, the system can exchange to another option as determined by user requirements. Keywords: low-quality connection; usersâ subjective perception; QoS parameter; QoS specification; resource availability;Â